2017
DOI: 10.1007/s12036-017-9460-y
|View full text |Cite
|
Sign up to set email alerts
|

Magneto–Thermal Evolution of Neutron Stars with Emphasis to Radio Pulsars

Abstract: The magnetic and thermal evolution of neutron stars is a very complex process with many, also non-linear, interactions. For a decent understanding of neutron star physics, these evolutions cannot be considered isolated. A brief overview is presented, which describes the main magneto -thermal interactions that determine the fate both of isolated neutron stars and accreting ones. Special attention is devoted to the interplay of thermal and magnetic evolution at the polar cap of radio pulsars. There, a strong mer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…. 5 × 10 6 K. Blackbody fits of thermal X-ray spectra provide radii Rpc of the emitting area, which is smaller by a factor ∼ 10 than the radius of the conventional polar cap R dip (see Table 1 in Geppert (2017)). Flux conservation arguments indicate that if R dip /Rpc ∼ 10, Bs ∼ 100B dip so that for a typical B dip ∼ 10 12 G Bs at the real polar cap is in the order of 10 14 G. Such field strengths cause a sufficiently high cohesive energy, in the cap surface layers, necessary for the creation of an electric potential gap sufficiently high to guarantee copious pair production.…”
Section: Introductionmentioning
confidence: 99%
“…. 5 × 10 6 K. Blackbody fits of thermal X-ray spectra provide radii Rpc of the emitting area, which is smaller by a factor ∼ 10 than the radius of the conventional polar cap R dip (see Table 1 in Geppert (2017)). Flux conservation arguments indicate that if R dip /Rpc ∼ 10, Bs ∼ 100B dip so that for a typical B dip ∼ 10 12 G Bs at the real polar cap is in the order of 10 14 G. Such field strengths cause a sufficiently high cohesive energy, in the cap surface layers, necessary for the creation of an electric potential gap sufficiently high to guarantee copious pair production.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a strong multipolar magnetic field is often invoked to explain X-ray thermal emission from areas that are apparently smaller than the polar cap area for a dipolar surface magnetic field. Recent compilations of polar cap radii from X-ray observed non-recycled pulsars have been used as strong observational evidence for a multipolar surface magnetic field (Geppert 2017;Rigoselli & Mereghetti 2018). We revisit the literature listed in these compilations and assess the robustness of their thermal polar cap area measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Fallback has also been invoked to explain the low magnetic field observed in central compact objects (CCOs), young neutron stars located near the centre of SN remnants. In this "hidden magnetic-field" scenario [238,239,240,241], the fallback material is able to bury the NS magnetic field explaining the observations of young NSs. In a longer timescale of 1 − 10 7 kyr, the magnetic field is able to re-emerge explaining magnetic fields in older objects [238,239,240].…”
Section: Iron Cores In Solar Metallicity Stars: Mass Dependence and Bmentioning
confidence: 99%
“…In this "hidden magnetic-field" scenario [238,239,240,241], the fallback material is able to bury the NS magnetic field explaining the observations of young NSs. In a longer timescale of 1 − 10 7 kyr, the magnetic field is able to re-emerge explaining magnetic fields in older objects [238,239,240]. Numerical simulations of the accretion of matter onto magnetised material have shown that this mechanism is indeed feasible [242,243,244,245,246,247].…”
Section: Iron Cores In Solar Metallicity Stars: Mass Dependence and Bmentioning
confidence: 99%